Young Children Learning from Touch Screens: Taking a Wider View - Lovato, Silvia B.; Waxman, Sandra R. (Frontiers in Psychology, 2016)
Touch screen devices such as smartphones and tablets are now ubiquitous in the lives of American children. These devices permit very young children to engage interactively in an intuitive fashion with actions as simple as touching, swiping and pinching. Yet, we know little about the role these devices play in very young children’s lives or their impact on early learning and development. Here we focus on two areas in which existing research sheds some light on these issues with children under 3 years of age. The first measures transfer of learning, or how well children use information learned from screens to reason about events off-screen, using object retrieval and word learning tasks. The second measures the impact of interactive screens on parent-child interactions and story comprehension during reading time. More research is required to clarify the pedagogical potential and pitfalls of touch screens for infants and very young children, especially research focused on capabilities unique to touch screens and on the social and cultural contexts in which young children use them.